2006
DOI: 10.1097/00001888-200602000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Challenges Facing Clinical Research: Solutions Proposed by Leaders of Medical Specialty and Clinical Research Societies

Abstract: The development of a robust national clinical research enterprise is needed to improve health care, but faces formidable challenges. To define the impediments and formulate solutions, the Institute of Medicine's Clinical Research Roundtable convened leaders from medical specialty and clinical research societies in 2003. Participants considered how to influence clinical research funding priorities, promote mechanisms to train physicians and other health care professionals to conduct clinical research, and how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 16 publications
2
45
0
1
Order By: Relevance
“…3 In recent decades, attempts to address this shortage have included formalizing research training during clinical years to ensure that it remains a career-long priority. 4 Several expert committees-including the NIH Director's Panel on Clinical Research, 5 the Institute of Medicine's Clinical Research Roundtable, 6 and the Association of American Medical Colleges' second Clinical Research Task Force (CRTFII) 7 -have generated recommendations and funding mechanisms for implementing clinical research education in the United States. Specific points highlighted by these expert panels include the need for a structured, didactic curriculum that incorporates a core knowledge base; practical clinical research experience; mentorship opportunities; protected research time for mentors; and formal recognition, such as a certificate or master's degree.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 In recent decades, attempts to address this shortage have included formalizing research training during clinical years to ensure that it remains a career-long priority. 4 Several expert committees-including the NIH Director's Panel on Clinical Research, 5 the Institute of Medicine's Clinical Research Roundtable, 6 and the Association of American Medical Colleges' second Clinical Research Task Force (CRTFII) 7 -have generated recommendations and funding mechanisms for implementing clinical research education in the United States. Specific points highlighted by these expert panels include the need for a structured, didactic curriculum that incorporates a core knowledge base; practical clinical research experience; mentorship opportunities; protected research time for mentors; and formal recognition, such as a certificate or master's degree.…”
mentioning
confidence: 99%
“…All of these panels emphasize the importance of introducing medical students and physicians to clinical research as early as possible in their training. [5][6][7] The creation of the National Eye Institute (NEI) in 1968 was a seminal event for vision research. The NEI legitimized the field of ophthalmic research, its research budget growing from $24 million in 1970 to $500 million in 2000 and to $708 million in 2017.…”
mentioning
confidence: 99%
“…Lastly, young physicians are carrying extreme burdens of debt accumulated during their medical education, whereas managed care has imposed constraints on the system of medical education for students (Ludmerer, 1999), residents, and fellows (at a time when resident hours are severely reduced; Education, 2002), and the numbers of nursing personnel are at an all time low (Aiken et al, 2002); the prospects of receiving good medical care have never looked more worrisome. Interestingly, a recent survey of physicians and patients reported that what concerned them most about today's health care was not medical errors but rather costs of malpractice, lawsuits, cost of health care, and the cost of prescription drugs (see Blendon et al, 2008;Murillo et al, 2006;O'Kane et al, 2008).…”
Section: The Crisis In Medical Care Cannot Be Ignoredmentioning
confidence: 99%
“…[22][23][24] Lack of a clinical research infrastructure, new regulations on the use of human subjects in research, and surprisingly, a ''lack of respect'' for clinical research involving human subjects were identified as impediments. [25][26][27] The ''lack of respect'' theme reemerged at a 2005 NIH-sponsored conference which discussed options for increasing and improving clinical research and appears to be the major reason for requiring an independent academic home (Center, Institute, Department) for clinical research in the NIH Request for Proposal for the Clinical and Translational Science Awards (CTSAs). CRTF II, which conducted its work at approximately the same time as the RFA for the Clinical and Translational Science Awards (CTSA) was issued, but before the first CTSA awards were made, addressed many of the same issues posed to the AACP Educating Clinical Scientist Task Force, particularly the appropriate type of education/training for a clinical scientist.…”
Section: The Physician Clinical Scientist Crisesmentioning
confidence: 99%